Birt–Hogg–Dubé syndrome. (17th September 2020) - Daccord, Cécile; Good, Jean-Marc; Morren, Marie-Anne; Bonny, Olivier; Hohl, Daniel; Lazor, Romain
Birt–Hogg–Dubé syndrome (BHD) is a rare inherited autosomal dominant disorder caused by germline mutations in the tumour suppressor gene FLCN, encoding the protein folliculin. Its clinical expression typically includes multiple pulmonary cysts, recurrent spontaneous pneumothoraces, cutaneous fibrofolliculomas and renal tumours of various histological types. BHD has no sex predilection and tends to manifest in the third or fourth decade of life. Multiple bilateral pulmonary cysts are found on chest computed tomography in >80% of patients and more than half experience one or more episodes of pneumothorax. A family history of pneumothorax is an important clue, which suggests the diagnosis of BHD. Unlike other cystic lung diseases such as lymphangioleiomyomatosis and pulmonary Langerhans cell histiocytosis, BHD does not lead to progressive loss of lung function and chronic respiratory insufficiency. Renal tumours affect about 30% of patients during their lifetime, and can be multiple and recurrent. The diagnosis of BHD is based on a combination of genetic, clinical and/or skin histopathological criteria. Management mainly consists of early pleurodesis in the case of pneumothorax, periodic renal imaging for tumour detection, and diagnostic work-up in search of BHD in relatives of the index patient. Birt–Hogg–Dubé syndrome is a rare genetic disorder characterised by multiple lung cysts, recurrent pneumothoraces, skin lesions and kidney tumours. As the presenting symptoms may be respiratory, chest physicians should be able to identify this disease. https://bit.ly/2xsOTuk